2002
DOI: 10.1038/nm0202-179
|View full text |Cite|
|
Sign up to set email alerts
|

Small molecule insulin mimetics reduce food intake and body weight and prevent development of obesity

Abstract: Obesity and insulin resistance are major risk factors for a number of metabolic disorders, such as type 2 diabetes mellitus. Insulin has been suggested to function as one of the adiposity signals to the brain for modulation of energy balance. Administration of insulin into the brain reduces food intake and body weight, and mice with a genetic deletion of neuronal insulin receptors are hyperphagic and obese. However, insulin is also an anabolic factor; when administered systemically, pharmacological levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 21 publications
2
80
1
3
Order By: Relevance
“…4C). Although each test is limited in its ability to detect aversive effects from a wide variety of causes, collectively these data strongly suggest that the antibody does not make animals sick (2). Thus, the reduction in food intake occurring 10 h after IMC-A1 injection is unlikely to be a manifestation of illness caused by nonspecific toxicity of the antibody.…”
Section: Possible Adverse Effectsmentioning
confidence: 92%
See 1 more Smart Citation
“…4C). Although each test is limited in its ability to detect aversive effects from a wide variety of causes, collectively these data strongly suggest that the antibody does not make animals sick (2). Thus, the reduction in food intake occurring 10 h after IMC-A1 injection is unlikely to be a manifestation of illness caused by nonspecific toxicity of the antibody.…”
Section: Possible Adverse Effectsmentioning
confidence: 92%
“…The conditioned taste aversion (CTA) test has been used to test the involvement of general malaise or illness in drug-induced reduction of appetite (2,55). To get the rats used to drinking saccharin, 18-h water-deprived animals were given brief access to saccharin solution (0.01% in distilled water).…”
Section: Aversion Testsmentioning
confidence: 99%
“…Studies using monkeys and rats have revealed that intracerebroventricular (icv) insulin administration diminishes the amount of food intake and body weight [16][17][18]. This food intake-lowering effect of insulin is reported to be reversed by the icv administration of PI3K inhibitor [19].…”
Section: Central Insulin Action and Glucose/energy Metabolismmentioning
confidence: 99%
“…The brain and cerebrospinal fluid contain insulin, but since the brain produces little or no insulin, it must come from the periphery, consistent with there being both high plasma and cerebrospinal fluid insulin in obese subjects (for review, see Woods & Seeley, 2001). Finally, a smallmolecular-weight insulin receptor agonist has been shown to reduce food intake and increase expenditure when given either centrally or peripherally, possibly because it penetrates the brain better than insulin (Air et al 2002).…”
Section: Tonic Indicators Of Fat Stores: Leptin and Insulinmentioning
confidence: 99%